The combination of Acalypha indica–Centella asiatica extracts decreases the neuronal damage in hypoxia-induced hippocampal injury animal model (Faculty of Medicine Universitas Indonesia, 2018)
Background: Approximately 80–85% of strokes are ischemic and lead to alterations in neuronal cell morphology and cell death. There is a lack of studies on the effect of the combination of Acalypha indica L. (AI) and Centella asiatica L. (CA) in terms of its neurotherapy property. This study was conducted to investigate the neurotherapeutic effect of the combination of AI–CA extracts in improving ratâs hippocampal neuron injury post-hypoxia.Methods: A total of 36 Sprague-Dawley rats were categorized into six groups and placed in a hypoxia chamber for 7 consecutive days. Then, they were moved to normoxia cages and treated for 7 consecutive days as follows: control group without treatment as a negative control; treatment groups were administered citicoline 50 mg/kgBW as a positive control; three different dose combinations of AI150–CA150, AI200–CA150, and AI250–CA150 mg/kgBW, respectively. Histological analyses were performed to assess the improvement in nerve cell damage in the hippocampus. Results: Treatment with citicoline significantly decreased the damage of nerve cells (30.8%); the combination of the AI–CA extracts of AI150–CA150, AI200–CA150, and AI250–CA150 also significantly decreased the damage of nerve cells (36%, 36.4%, and 30.4%, respectively) compared to the control rats (15.4%).Conclusion: The combination of AI–CA extracts decreased the neuronal damage in the hypoxia-induced hippocampal injury animal model. The improvement effect of the combination of AI–CA extracts was not significantly different to citicoline.